Pensamiento creativo : actividades estimulantes ¡increíbles! para niños de 6 a 12 años - Hussey, Will (Herramientas Narcea., 2017)
A compilation of activities designed to stimulate children to think creatively and to explore different ways of expressing new ideas more clearly.